(untitled) (Global Journal of Management and Business Research, 2023)
Abstract- This study aimed to assess the impact of the COVID-19 pandemic on the liquidity and profitability of commercial banks in Bangladesh The data of the fifteen selected banks were gathered from the financial statements for each quarter of four years from Q1 of 2018 to Q4 of 2021 encompassing the two years preceding and following the COVID-19 outbreak This study uses a comparative quantitative methodology to compare the liquidity and profitability of commercial banks in Bangladesh before and after the COVID-19 pandemic The results revealed that the profitability measured by return on asset ROA and return on equity ROE during post-pandemic times was more volatile than the pre-pandemic time but the trend is almost the same and the difference is statistically insignificant The liquidity positions of the banks have been measured by Cash ratio CaR current ratio CR credit-to-deposit ratio CDR debt-to-asset ratio DAR operating cash flow ratio OCFR and debt-to-equity ratio DER The results revealed that the pre and post-pandemic liquidity positions are significantly different except for the liquidity measures OCFR and DER The findings also confirmed that the COVID-19 pandemic has had a substantial detrimental effect on the liquidity of banks As a result of the recovery strategy planned by the central bank of Bangladesh the sample banks were able to mitigate the effects of the COVID-19 pandemic to a significant degree according to the findings of the study